PROBLEMATIKA PEMBELAJARAN SAINS DITINJAU DARI ASPEK GURU - Milya Sari (State Institute of Islamic Studies Imam Bonjol Padang, 2013)
Science Education in Indonesia is still poor. There are many components involved in science education such as the teacher. The myriad flaws of the teacher's factor must be addressed: the intake of low teacher, teachers' commitment, performance, the level of teacher education, etc. These are caused by low performance of the principal and the Superintendent and the policies of the Government.  To overcome these problems, then, it is necessary to improve the following program including training and tutorial programs, etc.  It is expected that through the efforts of increasing teacher's quality will improve students' science literacy.